2022
DOI: 10.1097/qai.0000000000003000
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic SARS-CoV-2 Infection Is Common Among ART-Treated People With HIV

Abstract: Background: Limited data are available regarding asymptomatic COVID-19 among people with HIV (PWH). Data on a representative subset of PWH enrolled in Randomized Trial to Prevent Vascular Events in HIV, a global clinical trial, are presented here. Methods:Randomized Trial to Prevent Vascular Events in HIV is an atherosclerotic cardiovascular disease prevention trial among 7770 PWH on antiretroviral therapy. Beginning April 2020, targeted data on coronavirus disease 2019 (COVID-19) diagnosis and symptoms were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…Epidemiological studies have shown the presence of pre-existing antibodies cross-reactive with SARS-CoV-2 in the serum of sub-Saharan African patients. This presence has been related to a lower COVID-19 morbidity/mortality in this populations [42] , [43] . Plasmodium and human immunodeficiency virus (HIV), both microorganisms being endemic in Africa, have been shown to induce in patients nNAbs that can cross-react with SARS-CoV-2, but these antibodies do not correlate with more severe forms of COVID-19 disease [44] , [45] , [46] .…”
Section: Sars-cov-2 and Ade: Mechanisms And Evidencementioning
confidence: 74%
“…Epidemiological studies have shown the presence of pre-existing antibodies cross-reactive with SARS-CoV-2 in the serum of sub-Saharan African patients. This presence has been related to a lower COVID-19 morbidity/mortality in this populations [42] , [43] . Plasmodium and human immunodeficiency virus (HIV), both microorganisms being endemic in Africa, have been shown to induce in patients nNAbs that can cross-react with SARS-CoV-2, but these antibodies do not correlate with more severe forms of COVID-19 disease [44] , [45] , [46] .…”
Section: Sars-cov-2 and Ade: Mechanisms And Evidencementioning
confidence: 74%
“…Unfortunately, patients with asymptomatic infection have low SARS-CoV-2 N antibody titers [ 40 ] and a possible infection occurring early in the pandemic could not be identified even in case of antibody testing. Furthermore, asymptomatic SARS-CoV-2 infection is common in patients with HIV infection [ 41 ] and it is possible that previously infected subjects were included, despite the criteria we applied to select only SARS-CoV-2 infection naïve individuals. Summing up, there could be uncertainty about whether natural infection could impact on IgG response at our study time points.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the COVID-19 cases observed in this study had no symptoms or mild symptoms (86.3%). Rial-Crestelo et al also observed a high proportion of patients with asymptomatic or mild disease in Spain (75.3% of 158 patients) [ 14 ], while a study in China showed 60% of 2464 PLHIV with COVID-19 infection being asymptomatic [ 16 ]. The proportion of severe and critical cases was smaller in our study (6.7%), which showed different patterns, although with limited numbers of COVID-19 cases in PLHIV.…”
Section: Discussionmentioning
confidence: 99%